The Cat Ate my Gymsuit - Danziger, Paula (Hodder Headline Plc, 1974)
Thirteen year old Marcy lacks self-confidence and feels weighed down by problems: she's afraid of her father, convinced she's so fat she'll never have a date, and bored by school. Then along, comes Ms Finney- a young, fun new teacher- and life takes on new meaning...
Keywords: Juvenile Fiction